Characterization of self-prestressing iron-based shape memory alloy bars for new structures. (31st March 2023) - Dong, Zhiqiang; Liu, Ziqing; Ji, Jianghao; Zhu, Hong; Wu, Gang; Sun, Changjun
Highlights: A new type of application method of Fe-SMA bars in new structures was proposed. The Fe-SMA bars can generate a prestress of 218–343 MPa in the concrete environment. The additional end thread anchorage system can improve the effective prestress of the Fe-SMA bar in concrete. A prediction model of the long-term prestressing retention of the Fe-SMA bar was proposed. Abstract: As a new type of material for prestressed strengthening, iron-based shape memory alloys (Fe-SMA) have been extensively studied by the Swiss Federal Laboratories for Materials Science and Technology (Empa) and used in many demonstration structural strengthening projects across Europe. However, research on Fe-SMA in new structures remains insufficient. Therefore, aiming at the application in new structures, this paper proposed a new application method by combining the Fe-SMA bar and the corrugated plastic pipe, i.e., placing the Fe-SMA bar into the corrugated plastic pipe and filled with high-temperature resistant mortar. The effects of the prestrain level, activation temperature, and additional end threaded anchors on the prestress generated in the Fe-SMA bar were tested. In addition, to analyze the difference between the concrete-covered environment and the air-exposed environment on the generated prestress, tests on bare Fe-SMA bars were performed. A prediction model of the long-term prestressing retention of the Fe-SMA bar was proposed based on the monitored data. The test results show that the Fe-SMA bars can generate a prestress of 218–343 MPa in the concrete environment. With the increase in prestrain level and activation temperature, the prestress generated in the Fe-SMA bar increases. The additional end thread anchorage system can improve the effective prestress of the Fe-SMA bar in concrete. In addition, the prestress loss mainly occurred in the early stage and gradually slowed down with time; for example, the prestress loss after activated for 24 h accounted for approximately 42.3%∼55.1% of the total loss in 1000 h. The prediction results show that the prestress retention of the Fe-SMA bar with a reasonable prestrain level and activation temperature can be stably maintained above 79% after 50 years of service.